Dermoscopy of Pitted Keratolysis - Lauren L. Lockwood; Samuel Gehrke; Alexander A. Navarini (Karger Publishers, 2010)
Irritated hyperhidrotic soles with multiple small pits are pathognomonic for pitted keratolysis (PK). Here we show the dermatoscopic view of typical pits that can ensure the diagnosis. PK is a plantar infection caused by Gram-positive bacteria, particularly Corynebacterium. Increases in skin surface pH, hyperhidrosis, and prolonged occlusion allow these bacteria to proliferate. The diagnosis is fundamentally clinical and treatment generally consists of a combination of hygienic measures, correcting plantar hyperhidrosis and topical antimicrobials.